2018
DOI: 10.1038/s41467-018-05559-w
|View full text |Cite|
|
Sign up to set email alerts
|

ZCCHC3 is a co-sensor of cGAS for dsDNA recognition in innate immune response

Abstract: Cyclic GMP-AMP synthase (cGAS) senses double-strand (ds) DNA in the cytosol and then catalyzes synthesis of the second messenger cGAMP, which activates the adaptor MITA/STING to initiate innate antiviral response. How cGAS activity is regulated remains enigmatic. Here, we identify ZCCHC3, a CCHC-type zinc-finger protein, as a positive regulator of cytosolic dsDNA- and DNA virus-triggered signaling. We show that ZCCHC3-deficiency inhibits dsDNA- and DNA virus-triggered induction of downstream effector genes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
102
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 46 publications
1
102
1
Order By: Relevance
“…However, production of both T1-IFN mRNA and protein, as well as protection against enhanced tissue pathology following VACV infection, was dependent upon cGAS, but not upon other PRR signaling pathways. This contrasts with other studies, which have demonstrated that cGAS is required to protect against VACV challenge, but which have stopped short of demonstrating a role for cGAS in T1-IFN production following VACV infection [18,37,38]. The lack of a link between cGAS and T1-IFN production following VACV infection in vivo likely stems from technical issues, and we developed a number of highly sensitive ex vivo approaches in order to be able to detect T1-IFN transcripts and protein from VACV-infected tissue.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…However, production of both T1-IFN mRNA and protein, as well as protection against enhanced tissue pathology following VACV infection, was dependent upon cGAS, but not upon other PRR signaling pathways. This contrasts with other studies, which have demonstrated that cGAS is required to protect against VACV challenge, but which have stopped short of demonstrating a role for cGAS in T1-IFN production following VACV infection [18,37,38]. The lack of a link between cGAS and T1-IFN production following VACV infection in vivo likely stems from technical issues, and we developed a number of highly sensitive ex vivo approaches in order to be able to detect T1-IFN transcripts and protein from VACV-infected tissue.…”
Section: Discussioncontrasting
confidence: 60%
“…Upstream of STING, cGAS has been implicated in the recognition of multiple virus infections, including VACV [18,37,38]. However, in addition to its well established role in induction of T1-IFN production, cGAS can also activate NF-B [39][40][41] and STAT6 [42,43], both of which can impact the anti-poxvirus immune response [44][45][46][47][48][49].…”
Section: Cgas Sensing Of Vacv-infected Cells Induces T1-ifn To Limit mentioning
confidence: 99%
“…We specifically selected 3’UTRs of interest to either B cell or EBV biology. These included (i) FOXO3, encoding Forkhead box O3a, a member of the conserved forkhead box transcription factors (53), (ii) RANBP9, encoding an adaptor protein that interacts with Zta to augment reactivation (54), (iii) YY1, necessary for GC reactions (55) and binds multiple sites within Zp to repress Zta expression (21), (iv) ZCCHC3, encoding a co-sensor for cGAS (56), and (v) ZEB2, a transcriptional repressor of Zp (13, 22). Binding sites in these 3’UTRs represented a range of 6mer (nt 2-7) to 8mer (nt 2-9) seed matches for miR-141-3p and/or miR-BART9-3p (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, we identified another common target of miR-141 and miR-BART9, ZCCHC3 (Fig. 5), that functions as a co-sensor for cGAS, activates the IFNbeta promoter, and contributes to innate immune responses directed against DNA virus infection in the cytosol (56). Overexpression of ZCCHC3 enhances herpes simplex virus 1 (HSV1) mediated activation of interferon response genes (56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation